التمكين الإداري وأثره في تحقيق الإبداع التنظيمي – حالة مؤسسة أنتيبيوتيكال فرع مجمع صيدال Administrative Empowerment And Its Impact On Achieving Organizational Innovation – Case Of Antibiotical Enterprise Branch Of Saidal Group - بودلة, يوسف; صلواتشي, هشام سفيان; كواديك, حمزة (Université de M'sila, 2019)
ملخص: هدفت الدراسة إلى قياس العلاقة بين تطبيق أسلوب التمكين الإداري لدى عينة مكونة من 44 مبحوث وأثره في تحقيق الإبداع التنظيمي في مؤسسة أنتيبيوتيكال – فرع مجمع صيدال بالمدية. لقد أظهرت نتائج الدراسة بإمكانية تطبيق أسلوب التمكين الإداري بدرجة جيدة على محاور الدراسة، كما أظهرت النتائج وجود فروق دالة إحصائيًا على محاور الدراسة تبعًا لمتغيرات (المستوى الدراسي والخبرة العملية)، مع وجود أثر ذو دلالة إحصائية عند مستوى (0.000**) لأبعاد المتغير المستقل "التمكين الإداري" (تفويض السلطة، فرق العمل، الإتصال ومشاركة المعلومات، التدريب، التحفيز)، على أبعاد المتغير التابع "الإبداع التنظيمي" (الأصالة، الطلاقة، المرونة، الحساسية). تصنيف JEL: L00، M10،O31. Abstract: The study aimed at measuring the relationship between the application of administrative empowerment for a sample of 44 administrators and its impact on the achievement of the organizational creativity at the Antibiotical enterprise Branch of SAIDAL Group of MEDEA. The results illustrated the possibility of applying the method of administrative empowerment with a good degree on the study axes, as its showed also the existence of statistically significant differences on the study axes according to (Level of study and practical experience), with a statistically significant effect at (0.000**) for the dimensions of the independent variable "administrative empowerment" with Organizational creativity. Keywords: Administrative Empowerment, Organizational Creativity, Participation in decision-making. Jel Classification Codes: L00, M10, O31.
Keywords: التمكين الاداري ; الابداع التنظيمي ; المشاركة في اتخاذ القرار